HELICOBACTER PYLORI-ASSOCIATED INFLAMMATION IN PATIENTS WITH ACUTE CORONARY SYNDROME - O. N. Pavlov (Klinicist)
The aim – assessment of the prevalence of seropositivity to Helicobacter pylori infection and laboratory comparative study of the peripheralblood in patients depending on the course of coronary heart disease (CHD).Materials and methods. Observation of 100 patients with coronary artery disease and 40 control patients is presented. Investigation indicatorsof clinical blood tests, biochemical blood analysis and determination of immunoglobulin antibody titer against Helicobacter pylori.Results. In patients with coronary artery disease signs of systemic inflammation associated with the development of acute coronary syndrome are marked with increased antibody titers to infection Helicobacter pylori.Conclusion. A history of coronary artery disease in patients with Helicobacter pylori-associated gastroduodenal pathology should be considered as a factor that increases the likelihood of unstable coronary desease course. Detected in patients with coronary artery disease signs of systemic inflammation with an increase in titer of antibodies to Helicobacter pylori infection associated with development of acute coronary syndrome.